The Counter‐Movement Through the Lens of Generation: Emancipation, Protection, and Neoliberalization in Costa Rica, 2000–2018. (18th November 2020) - Rayner, Jeremy; Morales Rivera, Valeria
Abstract: This article employs ethnography and history to consider the role of distinct age cohorts, or generations, in the emergence of powerful movements against neoliberalization in twenty‐first‐century Costa Rica, articulated around the defense of the "social state" and through a decentralized, horizontal organization practice. Utilizing Nancy Fraser's concept of the "triple movement, " we argue that attention to the politics of emancipation and of age cohorts or generations enriches our understanding of movements for social protection by drawing attention to the roles of life cycle and the formation of generations in reactions to marketization; the changing historical definition of what is deemed worth protecting from the market; and the importance of "emancipation, " both as a motive of political participation and as an organizational commitment that facilitates the articulation of intergenerational movements. Resumen: Este artículo emplea la etnografía y la historia para analizar el rol que distintas cohortes etarias o generaciones han tenido en el surgimiento de poderosos movimientos contra la neoliberalización en Costa Rica a comienzos del siglo XXI, articulados en torno a la defensa del "Estado social" y a través de la práctica organizativa horizontal descentralizada. Utilizando el concepto de Nancy Fraser del "movimiento triple, " planteamos que la atención a las políticas de emancipación y de cohortes etarias o generaciones, enriquece nuestra comprensión de los movimientos de protección social, al resaltar los roles del ciclo de vida y de la formación de generaciones en las respuestas a la mercantilización; la cambiante definición histórica de lo que se considera debe ser protegido del mercado y la importancia de la "emancipación, " tanto como motivo de participación política como compromiso organizacional que facilita la articulación de los movimientos intergeneracionales.